A Preliminary Evaluation of the Supervision With Immediate Enforcement Probation Program for Adult Gang–Affiliated Offenders in Texas. (July 2018) - Boots, Denise Paquette; Wareham, Jennifer; Stevens-Martin, Kelli; Barbieri, Nina
As of 2012, it was estimated that there were more than 30, 000 active gangs in the United States with at least 850, 000 members. Despite significant challenges that criminal justice agencies and personnel face in treating and supervising gang members, few studies have examined adult gang member outcomes and the effects of community supervision on gang-affiliated offenders. Recent research demonstrates mixed evidence that high-risk offenders have better outcomes in smaller problem-solving courts and programs, which have dual emphasis on rehabilitation and deterrence-based approaches to corrections. This study evaluates the efficacy of the Supervision with Immediate Enforcement (SWIFT) Court Program for young adult gang–affiliated probationers compared with non-SWIFT gang members and high-risk non-gang offenders. Findings indicated SWIFT had a moderate deterrent impact on offending compared with alternative probation sanctions. Results and discussion related to problem-solving courts and policy-related issues surrounding gang-affiliated and youthful violent offenders are offered.